First record of the hygropetric genus Oocyclus Sharp (Coleoptera: Hydrophilidae) from Laos, with description of a new species - Minoshima, Yûsuke (Zootaxa, 2009)
The genus Oocyclus Sharp, 1882 is recorded from Laos for the first time. Two species are recognized, including a new species: O. rupicola sp. n. and O. thailensis Short et Swanson, 2005. Male genital segments and female spermathecal organs are illustrated, and the latter is also described for each species. SEM photographs of several useful taxonomic features are provided. Digital photographs of the holotype of O. rupicola are provided (online version in color). A key to the species of the genus from the Indochina peninsula is given.